Komposisi, preferensi dan sebaran jenis tumbuhan pakan kakatua sumba (Cacatua sulphurea citrinocristata) di Taman Nasional Laiwangi Wanggameti - Oki Hidayat (Jurnal Penelitian Kehutanan Wallacea, 2014)
Sumba Cockatoo is an endemic bird and critically endangered in the island of Sumba. The population was declined drastically due to habitat degradation and illegal hunting. Management habitat activities such as enrichment important vegetation for Sumba Cockatoo has been made as in situ conservation ways. The purpose of this study was to determine the composition, preference and distribution of feeding plant species of Sumba Cockatoo at Laiwangi Wanggameti National Park. Vegetation analysis was made to know habitat characteristics by quadrat method with double compartment, with amount of 20 unit per location. The feeding preference was analyzed by Neu’s Method. The result showed that a total of 14 species were identified as food plants of the Sumba Cockatoo. The feeding plant spread uniformly at Praingkareha Forest Block and clumped at Billa and Mahaniwa. The most preferred food plant by Sumba Cockatoo were Lamo (Melia azedarach), Kayarak (Quercus piriformis) and Kepapang (Phaseolus lunatus) . All three have clumped distribution pattern.